Cassia auriculata L.: An Ethno Medical Approach in Exploring Anti-solar Efficacy - Randive, Krantisinha Hanumant; Hiremath, Ravindra Durdundayya; Kempwade, Amolkumar Ashok; Patil, Anagha Ashok (Indian Journal of Pharmaceutical Education and Research, 2019)
Objectives: The present study deals with an in-vitro screening for the anti-solar potential of aqueous and ethanolic extracts of Cassia auriculata using the UV method. Methods: Aqueous and ethanolic extracts were prepared. Thus, prepared extracts were subjected to phytochemical investigation and evaluated for antioxidant effect using DPPH and antisolar efficacy. Concentrations ranging from 7.8 to 1000 μg/mL (serial dilution) were used for the determination of radical scavenging effect and concentration of 2 mg/mL was used for screening of anti-solar potential using Shimadzu UV-1700 double beam UV-Visible spectrophotometer. Readings were recorded in triplicate and graphs were extrapolated. Results: Extracts revealed the presence of important phytoconstituents such as phenols, triterpenoids, flavonoids, tannins, saponins, phytosterols, alkaloids and glycosides. Further, it was observed that Cassia auriculata possesses remarkable antioxidant activity. Significant results of the anti-solar screening study confirm its use as a natural sunscreen. It showed a protective effect against carcinogenic UV radiation. Ethanolic extract was found to be more effective in comparison with aqueous extract. Conclusion: From the data, it can be concluded that aqueous and ethanolic extracts showed promising antioxidant and anti-solar activity which could be considered as a rational alternative to chemically prepared synthetic sunscreen formulations available in the market.
Keywords: Anti-solar; Carcinogenic; Cassia auriculata Linn; DPPH; SPF; UV